Acrylic and CPE modified PVC-U composites - effect of rice husk ash on impact properties - Hassan, Azman (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
PVC-U is an important material nowadays because of its widely used in construction and manufacturing as an alternative materials beside to wood and metal. The impact properties of PVC-U will become brittle once it is exposed to low temperature, subjected to high strain rate and occurrence of notching. The effects of using acrylic and chlorinated polyethylene impact modifiers, white rice husk ash (WRHA) and LICA 38 in PVC-U composites were presented in this research. Mixing was carried out by using a blender.PVC-U composites of different impact modifier and filler loading were compounded using two-roll mill and the specimens for impact strength testing was prepared using hot-press. Impact strength was measured according to Izod mode. The dimension for the specimens was according to ASTM D 256A on an Izod mode. Different composition of acrylic, CPE and WHRA were used in this study. As the impact modifier content was increased from 0 to 8 phr, impact strength increased steadily for both impact modifiers. As the filter content was increased from 10 to 30 phr, impact strength decreased steadily. It is interesting to observe that titanate-coupling agent (LICA 38) is successful in increasing PCV composites with 20 phr WRHA by 58.3% for acrylic modified PVC-U and by 21% by CPE modified PVC-U. This shows that LICA 38 is effective in enhancing the interfacial adhesion between WRHA and PVC-U matrix.